2008
DOI: 10.1152/physiolgenomics.90255.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamus transcriptome profile suggests an anorexia-cachexia syndrome in the anx/anx mouse model

Abstract: Mercader JM, Lozano JJ, Sumoy L, Dierssen M, Visa J, Gratacòs M, Estivill X. Hypothalamus transcriptome profile suggests an anorexia-cachexia syndrome in the anx/anx mouse model. Physiol Genomics 35: 341-350, 2008. First published September 23, 2008 doi:10.1152/physiolgenomics.90255.2008The anx/anx mouse displays poor appetite and lean appearance and is considered a good model for the study of anorexia nervosa. To identify new genes involved in feeding behavior and body weight regulation we performed an expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 82 publications
2
20
0
Order By: Relevance
“…In addition, the canonical pathways generated in our microarray analysis suggest that cell death and inflammatory processes occur in the hypothalamus of the anx/anx mouse. This finding is in agreement with previous studies suggesting inflammation and cell death in the anx/anx hypothalamus (10,15,35,36). The anx locus is still unknown.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the canonical pathways generated in our microarray analysis suggest that cell death and inflammatory processes occur in the hypothalamus of the anx/anx mouse. This finding is in agreement with previous studies suggesting inflammation and cell death in the anx/anx hypothalamus (10,15,35,36). The anx locus is still unknown.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, previous studies performed by us and others (Lachuer et al, 2005;Mercader et al, 2008) suggest an inflammatory response in anx/anx mouse that resembles to that observed in the anorexia-cachexia syndrome typically observed in cancer and human immunodeficiency virus or other chronic diseases (Tisdale, 2002).…”
supporting
confidence: 64%
“…Moreover, the anx mutation is linked to downregulation of the NADH dehydrogenase (ubiquinone) 1␣ subcomplex, assembly factor 1 (Ndufaf1), involved in the assembly of complex I (CI) in the mitochondrial oxidative phosphorylation system (OXPHOS), resulting in dysfunctional CI and increased oxidative stress (29). In addition, studies have demonstrated inflammation in the hypothalamus of the anx/anx mouse (26,35,37). Taken together, these observations provide an explanation for the hypothalamic dysfunction and neurodegeneration found in anx mutant mice (38).…”
mentioning
confidence: 75%